PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF GEOGEBRA TERHADAP HASIL BELAJAR MATEMATIKA MATERI MENGHITUNG LUAS DAN KELILING BANGUN DATAR SISWA KELAS V DI UPTD SDI BERTINGKAT PERUMNAS 3 - Selay, Astini; Damianus Dao Samo; Vera R. Bulu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Astini Selay NIM.2101140045 with the title "The Effect of Using GeoGebra Interactive Learning Media on Mathematics Learning Outcomes of Fifth Grade Students at UPTD SDI Bertingkat Perumnas 3". The problem in this study is to test the significant influence of the use of GeoGebra interactive learning media on Mathematics learning outcomes of fifth grade students at UPTD SDI Bertingkat Perumnas 3 Kupang City with the aim of improving student learning outcomes in mathematics learning about calculating the area and perimeter of flat shapes. This study uses a Quasi Experimental Design research type with a quantitative approach to the research design of Nonequivalent Control Group Design. The population in this study were 28 fifth grade students of UPTD SDI Bertingkat Perumnas 3 Kupang City. The sampling technique used was nonprobability sampling where the samples taken were 14 fifth grade students of A as the experimental class with treatment, and fifth grade students of B as the control class. Data collection techniques and instruments were questionnaires and test instruments. The research instrument was a test in the form of a pretest and posttest to measure learning outcomes. Before use, the instrument was first tested for validity and reliability. After data collection, it was analyzed and used to test the hypothesis. This research was conducted at the UPTD SDI Bertingkat Perumnas 3, Kupang City, for fifth-grade students. The results of the hypothesis testing, using a paired samples t-test, showed a significance value (2-tailed) of 0.001. This indicates that at the 2-tailed significance level (<0.05). In accordance with the decision-making basis, this is because the sig. value (2-tailed) <0.05 indicates a significant difference between the learning outcomes in the pretest and posttest data. Based on the above research results, it can be concluded that the use of GeoGebra interactive learning media has a significant effect on the mathematics learning outcomes of fifth-grade students at UPTD SDI Bertingkat Perumnas 3, Kupang City.